Validez y fiabilidad de la escala de participación de niños y adolescentes (CASP): una revisión sistemática - Roldán González, Elizabeth; Mera Mamián, Andry Yasmid; Bolaños Roldán, Ana Marcela; Suarez Muñoz, Lina Giccela (Retos, 2025)
Introduction: Participation is defined as voluntary involvement in everyday life situations. The Child and Adolescent Participation Scale (CASP) has been used to assess this construct, with its validity and reliability reported in various countries.Objective: This study analyzed the validity and reliability of the CASP scale, identifying its strengths and limitations.Methodology: A systematic review was conducted using the databases PubMed, Epistemonikos, Scopus, ScienceDirect, EBSCO, Wiley, LILACS, and WOS. Studies published between 2011 and 2023 were included.Results: The findings showed high ratings in aspects such as comprehensibility, relevance, and completeness, along with adequate internal consistency and intra- and interclass correlation. A positive correlation was also found with other instruments, such as the Child and Adolescent Factors Inventory (CAFI).Conclusions: The scale demonstrates strong psychometric properties. However, adjustments are needed to actively include infants and young people and to adapt the scale to diverse contexts, considering sociocultural, economic, educational, and labor factors.